2013
DOI: 10.1016/j.nano.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of size, surface coating and fine chemical composition on the in vitro reactivity and in vivo biodistribution of lipid nanocapsules versus lipid nanoemulsions in cancer models

Abstract: This study of lipid nanocapsules and lipid nanoemulsions compares their vitro and in vivo performance as a function of size and surface PEG chain length, demonstrating no significant difference among the tested particle sizes. Longer PEG chains on the LNE surface provided better stealth properties, whereas PEG modification on the LNC formulations inhibited the production of stable nanocarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…This obtained in vivo distribution is in line with the stability in human serum against the formation of high molecular weight aggregates. DLS analysis showed that only PS-LUT-NH 2 particles have a radius of < 100 nm in undiluted serum solution, which makes a longer and more efficient body distribution more likely [33]. Moreover, studies in whole blood showed a high uptake of this particle in monocytes as well as in granulocytes, whereas all other particles are only taken up in significant amounts in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This obtained in vivo distribution is in line with the stability in human serum against the formation of high molecular weight aggregates. DLS analysis showed that only PS-LUT-NH 2 particles have a radius of < 100 nm in undiluted serum solution, which makes a longer and more efficient body distribution more likely [33]. Moreover, studies in whole blood showed a high uptake of this particle in monocytes as well as in granulocytes, whereas all other particles are only taken up in significant amounts in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…administration [17], the clearance and biodistribution of lipid nanocapsules following administration to the lungs has not been reported. Since lipid nanocapsules may be developed as drug carrier systems for the treatment of lung conditions which are likely to be accompanied by inflammation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, DiD and Dil were used as probes because of their stability in LNCs, as has been previously observed in vivo and in vitro. 43 In the concentration range used, DiI and DiD brought a positive charge to the nanocapsules. It was relevant to use small nanocapsule quantities in mucus to study their stability in worst-case conditions, and thus we had to encapsulate a high amount of dyes, which unfortunately had an effect on the charge.…”
mentioning
confidence: 99%
“…6 The increase of particle size from 25 to 100 nm increased complement activation. 43 However, 25 nm LNCs quickly disappeared from the blood circulation. 46 As a consequence, 55 nm LNCs were chosen for diffusion studies in a function of their concentration.…”
mentioning
confidence: 99%